2015
DOI: 10.2147/ijn.s88317
|View full text |Cite
|
Sign up to set email alerts
|

Spherulitic copper–copper oxide nanostructure-based highly sensitive nonenzymatic glucose sensor

Abstract: In this work, three different spherulitic nanostructures Cu–CuO A , Cu–CuO B , and Cu–CuO C were synthesized in water-in-oil microemulsions by varying the surfactant concentration (30 mM, 40 mM, and 50 mM, respectively). The structural and morphological characteristics of the Cu–CuO nanostructures were investigated by ultraviolet–visible (UV–vis) spectroscopy, X-ray diffraction, scanning electron microscopy, and high-resolution transmission e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In all cases, the crystallinity was initially found to increase slightly and then decrease at longer periods of annealing. This indicates that at longer annealing times, nanosized crystals melt and recrystallize to some extent [ 51 , 52 , 53 ]. After this melting/recrystallization process, the size, perfection, or both of the crystallites are decreased due to the fact that the recrystallization process occurs in a completely different environment than the initial synthesis condition, which leads to a decline in overall crystallinity [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…In all cases, the crystallinity was initially found to increase slightly and then decrease at longer periods of annealing. This indicates that at longer annealing times, nanosized crystals melt and recrystallize to some extent [ 51 , 52 , 53 ]. After this melting/recrystallization process, the size, perfection, or both of the crystallites are decreased due to the fact that the recrystallization process occurs in a completely different environment than the initial synthesis condition, which leads to a decline in overall crystallinity [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Together, these results implied that the CuO/NOND/Pyr-Si sensor can feasibly be applied for rapid, accurate, and sensitive detection of glucose. The comparison of the analytical performance of CuO/NOND/Pyr-Si with several copper and nickel nanostructure-modified electrodes for glucose detection in terms of their response speed, detection limit (LOD), linear range, sensitivity, and stability is summarized in Table . …”
Section: Results and Discussionmentioning
confidence: 99%
“…Das et al reported in their study that when they examined the perphonation of CuO-modified biosensors, a rise in concentration resulted in an increase in sensitivity. The increase in sensitivity was due to a good electron transfer and load transfer [39]. CuO was used because of its easy accumulation on the PGE surface.…”
Section: Modification Of Electrodesmentioning
confidence: 99%